Increasing the Glen–Nye Power‐Law Exponent Accelerates Ice‐Loss Projections for the Amundsen Sea Embayment, West Antarctica - Benjamin Getraer; Mathieu Morlighem (Geophysical Research Letters, 2025)
Abstract Glacier flow is typically modeled using a power‐law rheology known as the Glen–Nye flow law, with the power n assumed to be 3. However, recent research and past observations suggest that n=4 may better represent ice flow in some locations. We lack a quantitative understanding of how much n affects ice‐loss projections, and its significance relative to other sources of uncertainty. Here, we test the effect of n=3 versus n=4 in a series of 300‐year forward simulations of the Amundsen Sea Embayment, West Antarctica. We find that in periods of rapid grounding line retreat, uncertainty in n leads to a larger spread in ice‐loss projections than the spread due to uncertainty in climate forcing. The spatial sensitivity of n is generally proportional to change in strain rates, so we expect regions undergoing more moderate dynamic change to be less sensitive to n.